PEMENUHAN HAK WARGA BINAAN PEREMPUAN YANG MEMILIKI ANAK BALITA DI LEMBAGA PEMASYARAKATAN KLAS IIB BENGKULU - Laksasmita, Claudia; Priyatmono, Budi (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Women's Prisons or LPP have different duties, especially for women. Even though they are different, they still protect the rights that must be protected. Criminal acts committed by women in the Bengkulu area do not escape the needs of the family. Sometimes people in the Bengkulu Class IIB Penitentiary are pregnant or have children aged 0 to 3 years. The Ministry of Law and Human Rights always strives for the rights of inmates, especially the rights of female inmates and respect for caring for their children in women's correctional institutions. Even though they are in a correctional institution and are carrying out punishment for mistakes committed by compensation, women are still women who are different from male compensation. Women menstruating, being pregnant and giving birth are privileges that men do not have. Especially women who care for and take their children to correctional institutions. Apart from caring for and providing breast milk, a mother's job is to care for and maintain the health of her child even in limited conditions in a correctional institution. Keywords: Woman; Children; Fulfillment of Rights